Ideal Formulation for Strengthening Mediation in Civil Dispute Resolution in Indonesia - Danial Syah; Herlina Hanum Harahap; Andri Winjaya Laksana; Ahmed Kheir Osman (Universitas Islam Sultan Agung, 2026)
Mediation as an alternative mechanism for resolving civil disputes in Indonesia still faces various challenges, despite having a strong legal foundation through Supreme Court Regulation (PERMA) Number 1 of 2016. This research analyzes the juridical, cultural, structural, and substantial aspects of civil dispute mediation and formulates an ideal model for strengthening its regulatory and institutional framework. The purpose of this study is to examine the legal basis, identify factors contributing to the low success rate, and propose an ideal formulation to strengthen mediation in civil dispute resolution in Indonesia. This research employs a doctrinal (normative legal) method and relies on secondary data obtained from literature sources. The findings indicate that mediation in civil dispute resolution in Indonesia has had a strong legal foundation since Article 130 of the Herzien Inlandsch Reglement (HIR) and has been reinforced through various Supreme Court regulations, including PERMA Number 1 of 2016. The low success rate of civil mediation in Indonesia is caused by a legal culture that prioritizes litigation, the uneven distribution of certified mediators, and the weak enforcement of sanctions under PERMA Number 1 of 2016 for parties acting in bad faith. The ideal formulation for strengthening mediation in Indonesia emphasizes revising PERMA Number 1 of 2016 to impose clearer and stricter sanctions for bad faith conduct, enhancing mediator capacity and public legal awareness, and optimizing electronic mediation (e-mediation) through PERMA Number 3 of 2022 to achieve an efficient, modern, and just dispute resolution system.